Vice-Chancellor Pay and Performance: The Moderating Effect of Vice-Chancellor Characteristics - Mohamed Elmagrhi (Work, Employment and Society, 2024)
This paper investigates the association between UK higher education institutions (HEIs) long- and short-term performance measures, and the pay of vice-chancellors/principals (VCs) in an era of intense neoliberalism/financialisation of HEIs, and consequently ascertains the extent to which the VC pay–performance nexus is moderated by VC characteristics. Using a longitudinal sample of UK HEIs, our baseline findings suggest that HEIs that prioritise meeting long-term social performance targets tend to pay their VCs low pay packages, whilst HEIs that focus on achieving short-term reputational performance targets pay their VCs high pay packages. We show further that the VC pay–performance relationship is moderated/explained largely by VC characteristics. Our findings are robust to controlling for alternative governance mechanisms, endogeneities, alternative performance measures and different estimation techniques. Our findings offer empirical support for optimal contracting and prestige theories with significant implications for the sector.